Author Correction: ARC6-mediated Z ring-like structure formation of prokaryote-descended chloroplast FtsZ in Escherichia coli - Hiroki Irieda (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. T he error has not been fixed in the paper.